Alteration in ATR protein level does not account for the inherent radiosensitivity of HPV-positive head and neck squamous cell carcinoma - Sibylla Kohl; Florentine S.B. Subtil; Vanessa Climenti; Houmam Anees; Ann C. Parplys; Rita Engenhart-Cabillic; Sebastian Adeberg; Ekkehard Dikomey; Ulrike Theiß (Translational Oncology)
Objectives: Human papilloma virus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) cells are highly radiosensitive resulting from an elevated number of DNA double-strand breaks (DSB) remaining after irradiation. Partially this effect is due to a defective homologous recombination (HR). HPV-positive cells also show pronounced instability of chromosome 3, which codes for the kinase ataxia-telangiectasia and Rad3-related (ATR) protein, a central player of HR. If there is a contribution of ATR to the radiosensitivity of HPV-positive cells remains unclear, and this in-vitro study tested a functional involvement of ATR expression. Methods: The study was performed with six HPV-negative and six HPV-positive HNSCC cell lines. Gene copy number and gene expression were determined via qRT-PCR, protein expression by Western Blot. Response of cells towards irradiation in dependence of ATR expression was tested after siRNA Knock-down (ATRKD). Clonogenic survival after photon irradiation was evaluated by colony formation assay and DSBs were visualized by γH2AX/53BP1 co-staining. Results: ATR gene copy number and expression were not altered. Protein level was almost two-fold lower in HPV-positive compared to HPV-negative cells, but fully functional as observed by active phosphorylation in response towards irradiation. ATRKD resulted in a further increase in both, radiosensitivity as well as number of residual DSBs, but only for HPV-positive cells. Conclusion: Since the effect of ATRKD was compensated in HPV-negative but not in HPV-positive cells, these data revealed that the two-fold lower level of ATR in HPV-positive cells does not account for their enhanced inherent radiosensitivity, but acts additive to irradiation.